2010
DOI: 10.1111/j.1365-2141.2010.08396.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L11 mutation in zebrafish leads to haematopoietic and metabolic defects

Abstract: Summary Mutations in ribosomal proteins are associated with a congenital syndrome, Diamond–Blackfan anaemia (DBA), manifested by red blood cell aplasia, developmental abnormalities and increased risk of malignancy. Recent studies suggest the involvement of p53 activation in DBA. However, which pathways are involved and how they contribute to the DBA phenotype remains unknown. Here we show that a zebrafish mutant for the rpl11 gene had defects both in the development of haematopoietic stem cells (HSCs) and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 46 publications
(58 reference statements)
13
124
0
Order By: Relevance
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015). Although apoptosis signals in the CHT region were decreased upon p53 deficiency, the proliferation signals between rpc9 −/− embryos with or without intact p53 signaling showed no significant difference, suggesting that increased apoptosis but not decreased proliferation was responsible for HSPC impairment in rpc9 mutants.…”
Section: Discussionsupporting
confidence: 70%
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015). Although apoptosis signals in the CHT region were decreased upon p53 deficiency, the proliferation signals between rpc9 −/− embryos with or without intact p53 signaling showed no significant difference, suggesting that increased apoptosis but not decreased proliferation was responsible for HSPC impairment in rpc9 mutants.…”
Section: Discussionsupporting
confidence: 70%
“…Other zebrafish studies have tested the role of p53 activation with conflicting results; a p53 morpholino rescues the hemoglobin defect in the rpL11 mutant, but does not rescue the defect induced by rps19 morpholino knockdown[16, 18]. Interestingly, morpholino knockdown of telomerase reverse transcriptase (TERT) in zebrafish embryos also causes apoptosis and hematopoietic specific defects[29].…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos homozygous for ribosomal protein mutations can survive for several days, likely the result of maternal RNA and protein contribution. Morpholinos against rps19 and rpL11[15-17], as well as an rpL11 mutant[18], recapitulate many aspects of the DBA phenotype, including hematopoietic specific defects and p53 activation.…”
Section: Introductionmentioning
confidence: 99%
“…o-Dianisidine staining has been reported previously (Danilova et al, 2011). TUNEL was performed using the In Situ Cell Death Detection Kit and TMR Red (Roche) according to the manufacturer's instructions.…”
Section: Morpholinos Mrna Synthesis and Microinjectionmentioning
confidence: 99%